2010
DOI: 10.1007/s00508-010-1492-0
|View full text |Cite
|
Sign up to set email alerts
|

A case series of 46 appendectomies during pregnancy

Abstract: The diagnosis of appendicitis in pregnancy is difficult, and the perforation rate is high. Particularly in term pregnancies, we recommend performing appendectomy immediately after cesarean section.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 22 publications
2
23
0
1
Order By: Relevance
“…So there might be a delay in its diagnosis that results in higher perforation rates in pregnant women. In the literature, perforation rates vary between 21.7-40% 6,7 . A perforated appendix is one of the most important surgical cause of fetal loss during pregnancy 8 and might cause peritonitis, sepsis and preterm labor 9 .…”
Section: Discussionmentioning
confidence: 99%
“…So there might be a delay in its diagnosis that results in higher perforation rates in pregnant women. In the literature, perforation rates vary between 21.7-40% 6,7 . A perforated appendix is one of the most important surgical cause of fetal loss during pregnancy 8 and might cause peritonitis, sepsis and preterm labor 9 .…”
Section: Discussionmentioning
confidence: 99%
“…[4,8] Furthermore, increasing gestational age reduces diagnostic accuracy and is associated with increased rates of appendiceal perforation and hence complications. [2,9] We operated the patients in our series within 12 hours. Contrary to the literature, in our study, there was no fetal loss or appendiceal perforation.…”
Section: Discussionmentioning
confidence: 99%
“…US and magnetic resonance imaging (MRI) are not associated with ionizing radiation, have not been shown to have any deleterious effects on pregnancy, and should be used when feasible. [4,[9][10][11] Retrospective studies have suggested that MRI of the appendix is useful in delineating the presence of appendicitis in pregnant women, but the small number of patients in these studies limits the inference that can be drawn. [12] There are also studies using computed tomography (CT) for the diagnosis of acute appendicitis in pregnancy; however, due to the deleterious effects of ionizing radiation on the fetus, it is suggested to be used only in severe trauma patients with pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…During pregnancy to diagnose acute appendicitis becomes harder or delays. According to some studies, appendix is observed normally in the %13-36 of all operations performed in 2nd -3rd trimester (6)(7)(8) . The most important reason that makes the diagnosis harder during pregnancy is the growth of the uterus which fills the pelvis and makes other pelvic organs move.…”
Section: Discussionmentioning
confidence: 99%
“…The perforation rates significantly increases after 24 hours from the beginning of the symptoms (9,10) . One study indicated a relation between perforation rates and further pregnancy weeks and also the time between the beginning of the symptoms and the operation time (p=0,027 and p<0,001 respectively) (8) .…”
Section: Discussionmentioning
confidence: 99%